Magnesium Technology 2001 2001
DOI: 10.1002/9781118805497.ch16
|View full text |Cite
|
Sign up to set email alerts
|

Solidification Behavior of Commercial Magnesium Alloys

Abstract: In this thesis, the solidification behavior of AZ91D, AM60B and AE44 commercial magnesium alloys has been studied experimentally by differential scanning calorimeter (DSC) and optical microscopy. The effect of different cooling rates on the transition temperatures and microstructures were analyzed. It was found that the effect of cooling rate on the solidus temperature is more significant than on the liquidus. The solidus temperature decreases clearly with increasing cooling rates, but for the liquidus tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
2
0
2
Order By: Relevance
“…the solid fraction formed by RSF at 613 °C, was estimated by optical microscopy to be ~36%: this result is in accordance with Ref. [6]. In every step, the microstructure was finer close to the casting surface than in the centre of the casting.…”
Section: Methodssupporting
confidence: 89%
“…the solid fraction formed by RSF at 613 °C, was estimated by optical microscopy to be ~36%: this result is in accordance with Ref. [6]. In every step, the microstructure was finer close to the casting surface than in the centre of the casting.…”
Section: Methodssupporting
confidence: 89%
“…Thermal analysis technique is a useful tool to obtain the value of phase-transformation temperature and heat of solidification of multicomponent alloys. Many researchers [1][2][3][4][5][6][7][8][9][10][11][12][13] studied the solidification behavior of magnesium alloys, but the effect of cooling rate on phase-transformation temperatures and enthalpy of solidification has not been investigated extensively in the literature. Hence, this work has been initiated to investigate experimentally the effect of cooling rate on phase-transformation temperatures and heat of solidification of the AZ91D, AM60B, and AE44 magnesium alloys using differential scanning calorimetry (DSC).…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted that for the same alloy AM60, Wei and Warren [21] and Barbagallo et al [19] reported different amount of Al content in the grain boundary region, and this is due to the fact that the casting conditions of the samples were different. Han et al [22] reported that for permanent mold casting of AZ91D alloy in the dendritic center the aluminum concentration is 2.6 wt.%, but it is 11.7 wt.% at the dendrite edge, about 4.5 times higher than that in the dendrite center. Zhang et al [23] conducted experiments to compare the amount of microsegregation in permanent mold cast and die-cast AZ91 alloys.…”
Section: Literature Datamentioning
confidence: 99%